Effect of silica-core gold-shell nanoparticles on the kinetics of biohydrogen production and pollutant hydrogenation via organic acid photofermentation over enhanced near-infrared illumination. (11th February 2021) - Ji, Yuxia; Sultan, Mansoor A.; Kim, Doo Young; Meeks, Noah; Hastings, Jeffrey Todd; Bhattacharyya, Dibakar
Abstract: A biological photoinduced fermentation process provides an alternative to traditional hydrogen productions. In this study, biohydrogen production was investigated at near IR region coupled to a near-field enhancement by silica-core gold-shell nanoparticles (NPs) over a range of acetate concentrations (5–40 mM) and light intensities (11–160 W/m 2 ). The kinetic data were modeled using modified Monod equations containing light intensity effects. The yields of H2 and CO2 produced per acetate were determined as 2.31 mol-H2 /mol-Ac and 0.83 mol-CO2 /mol-Ac and increased to 4.38 mmol-H2 /mmol-Ma and 2.62 mmol-CO2 /mmol-Ma when malate was used. Maximum increases in H2 and CO2 productions by 115% and 113% were observed by adding NPs without affecting the bacterial growth rates (6.1–8.2 mg-DCM/L/hour) while the highest hydrogen production rate was determined as 0.81 mmol/L/hour. Model simulations showed that the energy conversion efficiency increased with NPs concentration but decreased with the intensity. Complete hydrogenation application was demonstrated with toxic 2-chlorobiphenyl using Pd catalysts. Highlights: Biohydrogen and CO2 production rate quantified with two organic acid substrates. Enhancement of H2 productions by plasmonic NPs at near IR without affecting bacterial growth rates. Biohydrogen production showed constant rate under the stationary growth phase. Data analyzed by modified Monod-type kinetics containing light intensity effects. Hydrogenation of chloro-organic by Pd catalysts using produced biohydrogen.